Peningkatan Ekonomi Kreatif Melalui Pendampingan dan Edukasi Usaha - Ima Rahmawati; Hana Lestari; Nurdin Fahrurrobi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2022)
This community service activity (PKM) aims to provide education and assistance for Economic Actors in Sukajaya Village, Bogor Regency, by providing education on understanding and adequate counseling about the creative economy. The implementation of PKM activities starts from September 10 to October 9, 2021. The method of implementing PKM activities in Sukajaya Village is in two ways, namely in the form of direct services in the form of (1) SME Assistance, and (4) Handcrafts (Handicrafts), and indirect services in the form of (1) Economic Seminars, (2) Hydroponic Planting. The results obtained from these activities are an increase in public knowledge about the creative economy, compiling business financial reports, and having an understanding of tips on how to do business, especially for young people. Success in the implementation of activities can be seen from the high participation of citizens in our activities.